PENGARUH STRUKTUR KEPEMILIKAN SAHAM DAN CORPORATE SOCIAL RESPONSIBILITY PADA NILAI PERUSAHAAN - Adnantara, Komang Fridagustina (Buletin Studi Ekonomi; VOL.18.NO.2.AGUSTUS 2013. (PP 85-190), 2014)
Abstract : The Effect of Stock Ownership Structure and Corporate Responsibility in Corporate Values. The purpose of this research was to determine the effect of ownership structure on CSR, the effect of Ownership Structure on Firm Value, the effect of CSR on Firm Value, and indirect effect of Ownership Structure on Firm value through CSR. This research was conducted at manufacturing companies listed on the Indonesia Stock Exchange in the period 2008-2010. The sample used by 47 samples. The statistical method that used was the path analysis method. The results showed that the Institutional Ownership and Public Ownership has a positive effect on CSR, and CSR has a proven positive effect on Firm Value. It can be concluded that there is no direct effect of the Ownership Structure on the Firm value, but through CSR, Institutional Ownership and Public Ownership has indirect effect on the Firm Value.
Keywords: CSR, Firm Value, Ownership Structure